Analysis of Network Governance Practices and Social Responsibility (CSR) in First Middle School - Etty Indraswati (Journal of Social Research, 2023)
This study discusses network governance in educational institutions in order to show ethical performance (profile), and how to interact and collaborate with stakeholders. The governance cycle of educational institutions is directed at three dimensions, namely improving the performance and performance of the institution (performance improvement and enhancement), increased interaction with stakeholders (improvement in interaction with stakeholders), and qualitative improvement of the institution's core business qualitative improvements of the core business for Satisfaction with the quality of performance and services of schools/educational institutions. Good governance will have a positive impact on improving the quality of character education, and ethical culture so that schools have competitiveness. The results of this study are also direct social responsibility (CSR) educational institutions with ISO 26000 and their contribution to the SDGs that have not been implemented in educational institutions so that they become a reference for educational institutions to realize sustainable, effective and quality governance so that they are competitive.